RELATIONSHIP OF NUTRITIONAL STATUS, NUTRITIONAL INTAKE AND HISTORY OF DISEASE WITH WORK FATIGUE IN INFORMAL SECTOR RICE FARMERS IN TEUPIN PANAH VILLAGE, ACEH BARAT REGENCY - Dharma Andika Yudha; Fitriani Fitriani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study aims to determine the relationship between nutritional status, nutritional intake and history of disease with work fatigue in informal sector farm workers. The type of research used is analytic observation using the Cross Sectional research method. Time and location This research was carried out in Gampong Teupin Panah, Kaway XVI District, Aceh Barat Regency, Aceh in 2022. It was carried out in January - May 2022, Total population of 30 rice farmer workers . Based on the results of this study, the history of illness in the informal sector farm workers of Gampong Teupin Panah is not related to work fatigue because this may be due to other factors, namely the health condition and nutritional status of farm workers at the time of the study. Even though the rice farmer workers have a history of disease, the disease may have been experienced for quite a long time and at the time of the research their health condition was in good condition and their nutritional status was adequate. The calories needed to work are still balanced with the work done so that even though the rice farmer workers have a history of illness, it does not affect their work ability. The conclusion of this study is that work fatigue in informal sector rice farmer workers has high work fatigue by 80% or 24 of 30 respondents experience high work fatigue. The calories needed to work are still balanced with the work done so that even though the rice farmer workers have a history of illness, it does not affect their work ability. The conclusion of this study is that work fatigue in informal sector rice farmer workers has high work fatigue by 80% or 24 of 30 respondents experience high work fatigue. The calories needed to work are still balanced with the work done so that even though the rice farmer workers have a history of illness, it does not affect their work ability. The conclusion of this study is that work fatigue in informal sector rice farmer workers has high work fatigue by 80% or 24 of 30 respondents experience high work fatigue.